An intelligent web recommendation system for ubiquitous geolocation awareness. (9th September 2013) - Boutas, Sotirios D.; Anagnostopoulos, Ioannis E.; Loumos, Vassili; Kayafas, Eleftherios
Because of the rapid development of World Wide Web in recent years, it has become the basic source of information for millions of people around the world. However, the huge volume of data transferred through the web often causes confusion to users, who are often unable to select the kind of information that is actually suitable to their needs. This is where ubiquitous computing techniques should provide relevant information regarding products and services related to the users' needs. This paper presents such a system, the main goal of which is to select among a set of users, those who are most likely to be interested in specific events. For our approach, we employed a ubiquitous information system along with web 2.0 geospatial API technology and we tested it over simulated and real–life data.